Anisotropic constitutive model and numerical simulations for crystalline energetic material under shock loading. (August 2014) - Pi, Aiguo; Huang, Fenglei; Wu, Yanqing; Zhang, Zhongya
A dynamic crystal plasticity model for a low-symmetric β -cyclotetramethylene-tetranitramine single crystal with only limited operative slip systems has been developed, accounting for nonlinear elasticity, volumetric coupling with deviatoric behavior and thermo-dynamical consistence. Based on the decomposition of the stress tensor, a modified equation of state for anisotropic materials is employed. Simulations of the planar impact on the β -cyclotetramethylene-tetranitramine single crystal show good agreement with existing particle velocity data in the case of (110) and (011). Pressure snapshots, the dislocation density, the shear stress and the strain localization for β -cyclotetramethylene-tetranitramine single crystal under shocked loading are discussed. The present model provides more insights into a range of complex, orientation-dependent elastic and inelastic behaviors in shocked explosive crystals than isotropic elastic–plastic constitutive descriptions. The proposed formulation and algorithms can also be applied to study other low-symmetric crystals under high-pressure shocked loading that deform mainly by crystallographic slip.